Classification scheme of sacred landscapes - V. MISHCHENKO, Olena (European Journal of Geography, 2019)
The given research has an interdisciplinary character, as it covers a wide range of issues related to various sciences: geography, culture, philosophical anthropology. The purpose of the study is to justify the author’s classification scheme of sacred landscapes. In the research work a systematic approach to the study of sacred landscapes as a holistic organized territorial system and a set of methods, in particular: structural-logical generalization and system analysis, comparative-geographical, historical-geographical was used This article examines the meaning of the notion of sacred landscape, which in its content is wider than the religious landscape and is treated as a natural, natural-anthropogenic, anthropogenic system, associated with certain life symbols, myths, significant events, religious feelings, is extremely valuable to a person or group of people and requires special treatment and protection. The existing scientific experience concerning classification of religious territories and objects is generalized and the classification scheme of sacred landscapes was outlined on the following grounds: level of organization (individual, local, regional, national, global), time variability (paleocultural, historical and cultural), genesis (natural and naturalanthropogenic, anthropogenic). The proposed classification scheme is based on the ranking of the signs of territorial systems and their sacral components (territories and objects), which were determined due to the peculiarities of the structure, peculiarity of evolutionary development and functional purpose.